2018
DOI: 10.21608/jabps.2018.5175.1022
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects against early cardiomyopathic changes-induced by Type-1 diabetes through a heme-oxygenase-1 dependent mechanism

Abstract: Diabetes mellitus can be considered as a state of chronic inflammation and oxidative stress. Excessive oxidative stress is implicated in the pathogenesis of diabetic complications. Heme oxygenase-1 is an antioxidant enzyme that is upregulated in response to a variety of insults as a protective mechanism. Resveratrol (RSV) is a polyphenol that exhibits promising pharmacological effects in a variety of disease models. In this study, we investigated the role of RSV in prevention of early pathological changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, genetic restoration of HO-1 expression in DCs from NOD mice reduces T1D incidence highlighting their role in tolerizing autoreactive T-cells (249). It has been shown that resveratrol administration in drinking water attenuates biochemical changes associated with diabetes, and this protective role is mediated by TGF-β reduction and HO-1 induction (235).…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Interestingly, genetic restoration of HO-1 expression in DCs from NOD mice reduces T1D incidence highlighting their role in tolerizing autoreactive T-cells (249). It has been shown that resveratrol administration in drinking water attenuates biochemical changes associated with diabetes, and this protective role is mediated by TGF-β reduction and HO-1 induction (235).…”
Section: Type 1 Diabetesmentioning
confidence: 99%